ASPECTE EPISTEMOLOGICE ŞI PRAXIOLOGICE ALE EDUCAŢIEI ADOLESCENŢILOR PENTRU TIMPUL LIBER ÎN CONTEXTUL PARTENERIATULUI EDUCATIV - USM ADMIN (Moldova State University, 2008)
The article reflects the theoretical aspects of adolescents' education for useful spending of free time in the context of educational partnership. This problem is analyzed taking into account the functions and forms of education, the theory of new educations and coping strategy.